Length-Dependent Activation of Contractility and Ca-Transient Kinetics in Auxotonically Contracting Isolated Rat Ventricular Cardiomyocytes - Lookin, Oleg; Protsenko, Yuri (Frontiers in Physiology, 2019)
Length-dependent activation (LDA) of contraction is an important mechanism of proper myocardial function that often blunted in diseases accompanied by deficient contractility and impaired calcium homeostasis. We evaluated how the extent of LDA is related to the decreased force in healthy rat myocardium under negative inotropic conditions that affect the calcium cycle. The length-dependent effects on auxotonic twitch and Ca-transient were compared in isolated rat ventricular cardiomyocytes at room (“25C”) and near-physiological temperature (“35C”) in normal Tyrode and at 25C with thapsigargin-depleted sarcoplasmic reticulum (“25C+Thap”). At the slack length, a similar negative inotropy in “35C” and “25C+Thap” was accompanied by totally different changes in Ca-transient amplitude, time-to-peak and time-to-decline from peak to 50% amplitude. End-systolic/end-diastolic tension-sarcomere length relationships were obtained for each individual cell, and the ratio of their slopes, the dimensionless Frank-Starling Gain index, was 2.32±0.16, 1.78±0.09 and 1.37±0.06 in “25C”, “35C” and “25C+Thap”, respectively (mean ± S.E.M.). Ca-transient diastolic level and amplitude did not differ between “25C” and “35C” at any SL, but in “35C” it developed and declined significantly faster. In contrast, thapsigargin-induced depletion of SERCA2a significantly attenuated and retarded Ca-transient. The relative amount of Ca2+ utilized by troponin C, evaluated by the integral magnitude of a short-lived component of Ca-transient decline (“bump”), increased by 25% per each 0.05 μm increase in SL in all groups. The kinetics of the Ca-TnC dissociation, evaluated by the bump time-to-peak, was significantly faster in “35C” and slower in “25C+Thap” vs “25C” (respectively, 63.7±5.3% and 253.6±8.3% of the value in “25C”, mean ± S.E.M.). In conclusion, a similar inotropic effect can be observed in rat ventricular myocardium under totally different kinetics of free cytosolic calcium. The extent of LDA is not determined by actual peak systolic tension, but is regulated by the level of peak systolic calcium and the kinetics of Ca-transient decline that, in turn, are governed by Ca-TnC dissociation and Ca2+ reuptake by the sarcoplasmic reticulum. Altogether, these findings constitute new evidence about the role of length-dependent modulation of Ca2+ homeostasis in the mechanisms of calcium regulation of contraction and mechano-calcium feedback in the myocardium.